Atuação de oligoquetas e raízes na migração de calcário em solo ácido - Cassel, Júlia Letícia (2025)
Soil acidity in the subsurface is still a problem in no-tillage systems. Bioturbation through the action of roots and earthworms can be a promising process in soil correction in depth, as long as it is well understood. The objective of the study was to evaluate whether the migration of limestone particles can be favored by the root system and the presence of earthworms. An experiment in pots, in a completely randomized design, with four replications, received limestone on the surface. Five kilograms of acidic soil (pH: 5.08) from the A horizon of a humic dystric Red Latosol were used per experimental unit, represented by a vase. The treatments were: natural soil (SN), autoclaved soil with limestone (SA+C), natural soil with limestone (SN+C), natural soil with limestone and earthworms Eisenia fetida (SN+C+M), natural soil with limestone and Pennisetum glaucum roots (SN+C+R), natural soil with limestone, earthworms and roots (SN+C+M+R), natural soil with roots (SN+R) and natural soil with earthworms (SN+M). At the end of the experiment, which was conducted for 6 months, the earthworms were quantified and had their biomass accounted for. The total chemistry of the earthworms and mineralogy were determined, seeking to detect calcite and dolomite. The collection of soil samples was stratified in the pot (2 in 2 centimeters for chemical analysis and 5 in 5 centimeters for physical analysis). The chemical properties (active and potential acidity and tors of Ca, Mg and Al) and physical properties (particle and apparent density, total porosity and volumetric moisture in field capacity) were evaluated. As a result, the treatment with the presence of a root system showed higher porosity and lower soil density, where dolomite was identified in the 10-12 cm layer. The presence of earthworms increased the density of soil particles. Through the chemical and mineralogical analysis of the earthworms, it was identified that they feed on limestone and are capable of producing calcium carbonate. The bioturbation process promotes the biological incorporation of particles into the soil. Soil acidity correction was observed up to 8 cm depth. The work suggests that biological activity is a promising tool for the incorporation of limestone into the soil.